HUBUNGAN KELENGKAPAN INFORMASI REKAM MEDIS DENGAN KEAKURATAN KODE DIAGNOSIS DI RUMAH SAKIT - Andra Dwitama Hidayat; Krisnita Dwi Jayanti; Dianti Ias Oktaviasari; Intan Ayudya Novitasari (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
Accuracy in determining the diagnosis code was something that must be considered, an accurate code was obtained with information that was able to support the coder in determining the diagnosis code. The accuracy of diagnosis codes was very important in the fields of education, research, national health statistics, quality of hospital services, and the basis for decision-making. This study aims to analyze the relationship between completeness of medical record information and accuracy of the diagnosis code in the hospital. The method used descriptive analytic with a retrospective approach. The study population consisted of 6,069 inpatient medical record documents with a sample of 375 documents taken using simple random sampling technique. Based on the results of statistical tests using Chi-square, a p value of was obtained that there was a relationship between the completeness of medical record information and the accuracy of the diagnosis code at the hospital. Evaluation of the completeness of each medical record documents for a certain period of time was highly recommended to improve the accuracy of the diagnosis code.